Association of physical activity, body mass index and reproductive history with breast cancer by menopausal status in Iranian women. (August 2020) - Maleki, Farzad; Fotouhi, Akbar; Ghiasvand, Reza; Harirchi, Iraj; Talebi, Ghazaleh; Rostami, Sahar; Hosseini, Mostafa; Rozek, Laura; Zendehdel, Kazem
Highlights: Breast cancer tended to be inversely associated with high levels of physical activity. BMI modified the association between physical activity and breast cancer. High-level physical activity was protective in the normal-weight premenopausal women, and in the obese postmenopausal women. Postmenopausal overweight and obese women had a higher risk of breast cancer. Abstract: Background: The incidence rate of breast cancer (BC) is increasing in low- and middle-income countries (LMICs), including Iran. We investigated the association between BC risk and physical activity (PA), body mass index (BMI), and reproductive history among Iranian women. Methods: We conducted a large hospital-based case–control study and compared 958 BC cases with 967 controls at the Cancer Institute of Iran during 2011–2016. We used multiple logistic regression models and adjusted for potential confounders to estimate odds ratios (ORs) and 95% confidence intervals (95%CIs) for the associations between BC and different risk factors, including low physical activity. Results: Women with high levels of physical activity had a lower risk of BC compared to those who were inactive (OR = 0.55, 95%CI: 0.41, 0.75). In premenopausal women, the association was observed only in normal-weight women (OR = 0.31, 95%CI: 0.13, 0.75), while it was limited to obese women in the postmenopausal group (OR = 0.29, 95%CI: 0.12, 0.66). We found a high risk of postmenopausal BC among overweight (OR = 1.69; 95%CI: 1.01, 2.81) and obese women (OR = 1.9; 95%CI: 1.14, 3.14) compared to women with a normal BMI. We observed an inverse association among postmenopausal women who had between three and five children (OR = 0.31, 95%CI 0.14, 0.64) and more than six children (OR = 0.21, 95%CI 0.12, 0.42) compared to nulliparous women. Conclusions: Low levels of physical activity, low parity, and being overweight or obese were major risk factors for BC. For the first time, we report a strong association between physical activity and BC risk in Iranian women.